Estudos de Novas Metodologias Sintéticas para Heterocíclicos Quinolônicos, Triazólicos e Síntese de Catalisadores Quirais - Alves, Thatyana Rocha (2004)
In order to obtain quinolone nucleosides a new methodology based on construction of the heterocyclic ring at the carbohydrate moiety was devised. The carbohydrates: 1-methoxy-2,3-O-isopropylidene-α-D-ribofuranose (108), 1-methoxy-2,3-O-isopropylidene-5-O-methanesulfonyl-β-D-ribofuranose (109a) and 1-methoxy-2,3-O-isopropylidene-5-O-p-toluenesulfonyl-β-D-ribofuranose (109b) were prepared. The last two, the mesyl and tosyl derivatives, were submitted to nucleopilic substitution reaction with aniline or its corresponding anion, leading to 1-methoxy-2,3-O-isopropylidene-5-anilino-β-D-ribofuranose (110) in very low yield. Attempts to improve this yield by changing reaction conditions such as the polarity of the solvent or nitrogen eletronic density were unsuccessful. It seems that the elimination process is the most favorable under these conditions in the ribofuranoside ring.Also, the aldehyde 126 was prepared in order to produce 110 throught reductive amination reaction. Although, this synthesis has failed. Reaction of the amine 110 with diethyl ethoxymethylene malonate didn`t lead to ethyl N-phenyl-2,3-O-isopropilydene-ribofuranoside-α-carbethoxy-β-(anilino)acrylate (111), probably due to steric effects around the nitrogen. In the search for obtaining new quinolonic 2’,3’-didehydro-ribonucleosides (type II), several intermediates were prepared by using a methodology optimized in our group, which involves coupling previous sylilated 3-carbetoxy-4(1H)quinolones (X= F, 116a and X = Me, 116b) by reaction with N,O-bis(trimethylsilyl)trifluoracetamide (BSTFA), with 1-O-acetyl-2’,3’,5’,-tri-O-benzoyl-β-D-ribofuranose (23),under trimethylsilyltrifluormethanesulfonate (TMSO-Tf) catalysis. 3-Carbethoxy-1-(2’,3’,5’,-tri-O-benzoyl-β-D-ribofuranosyl)-4(1H)quinolone 117a-b were obtained in 83 and 85% yields, respectively. The acrylates 115a-b used to prepare the corresponding quinolones 116a-b were synthesized in 85 and 75% yields by a procedure described in the literature. The benzoyl protecting groups of the ribonucleosides 117a-b were removed by using methanolic sodium carbonate solution leading to the unprotected 3-carbomethoxy-1-β-D-ribofuranosyl-4(1H)quinolones 118a-b in 75% and 69% yields. These ribonucleosides were submitted to bromination and acetylation. Ribonucleoside 118b formed a 3:1 mixture of 2`-O-acety-3`-bromo and 3`-O-acety-2`-bromo regioisomeric derivatives. However, the same reaction with 118a produced the 2’,3’,5’-tri-O-acetylated derivative. Attempts to perform β-elimination reaction of the bromo-acetate ribonucleoside 118b to obtain the desired didehydro-nucleosides, using as reagent nickel deposited on charcoal surface were unsuccessful.Continuing our search for new heterocyclic nucleosides was investigated the preparation of triazolic derivatives (type III). The synthetic route devised started by preparing the aminocarbohydrates 129, 147, 150, 156 and 156, by a standard procedure described in the literature. These amino derivatives were reacted with diazomalonaldehyde (132) and diazoacetylacetone (133) affording 4-formyl-1,2,3-triazole-1-yl (130a e 148a) and 4-acetyl-5-methyl-1,2,3-triazole-1-yl (130b, 148b and 152a). The triazolic nucleoside 130a was tested against Herpes simplex virus type 1 (HSV-1) showing a good inhibition of the virus (86%) at the concentration 50 µM. Biological evaluation of this substance against HIV-1 virus is under study. All the nucleosides synthesized are also being tested against HSV-1 and HIV-1 virus. As an extension of our study on carbohydrate derivatives we undertook a search for new chiral Lewis acids based on stannylated carbohydrates. With this purpose we planned the preparation of the chiral Lewis acids 157a, 158a e 163a. Three reactions between tosylated carbohydrates 109b, 121 and 145 and Ph3SnLi were attempted. However, only carbohydrate 109b led to 1-methoxy-2,3-O-isopropylidene-5C-triphenylstannyl-α-D-ribofuranose (157a). In contrast, the reaction of Ph3SnLi with 121 produced 4,5-anhydro-1,2-O-isopropylidene-α-D-xylofuranose, rather than the stannylated substitution product. The carbohydrate 145 failed to produced any desired product. Thus it appears, superficially at least, that Ph3SnLi is acting as a nucleophille with 109b and as a base towards 121, eliminating p-MeC6H4SO3H. The lack of reactivity of 145 results from the steric hindrance by 3-sulfonate group difficulting the approach of the bulky tin-lithium reagent in an SN2-type reaction. Reactions of 157a with iodine, at both 1:1 and 1:2 mole ratios of 157a:I2, proceeded at ambient temperature to give the iodophenylstannylated products, 157b and 157c, in good yields. The chiral Lewis acids 157a-c were used in Diels-Alder reactions between methyl acrylate (122) and cyclopentadiene (123). The aduct 124 which was formed in the presence of 157c had its optical rotations measured. Chiral Lewis acid 157c was able to induce chirality leading to S configuration adduct as the major enantiomer (91% of enantiomeric excess). During the study on Diels-Alder reaction we had the opportunity to get a chiral catalyst, the fluoro-bis-oxazolidine 164 synthesized by Prof. Denis Sinou of Université Claude Bernard-Lyon I. We prepared in situ a copper complex of this compound and it was used in the Diels-Alder reaction between methyl acrylate (122) and cyclopentadiene (123). The result indicated that this catalyst was able to induce chirality in the cycloaduct favoring the S enantiomer (87% of enantiomeric excess).